Experimental Study of Natural Convection Heat Transfer on A Vertical Cylinder with Varying Heat Flux - Rakasiwi, Galih; Khoirudin, Khoirudin; Supriyanto, Agus (ROTASI, 2024)
The most commonly used heat transfer in cooling and heating systems is convective heat transfer. Natural convection heat transfer is typically employed in cooling systems with immersion cooling such as in data centers and transformers. In addition to cooling systems, natural convection is also utilized in heating systems as seen in nuclear reactors. More specifically, natural convection around heated cylinders has widespread applications. The flow of natural convection around vertical heated cylinders is a critical concern in various applications, including vertical tubes within HVAC systems, the heating of electronic components, and the storage of nuclear rods in waste facilities. In this study, a test apparatus in the form of a box measuring 300x200x150 mm with a 650-watt heater installed in the center was used. The heater is jacketed with an outer diameter of 38mm and a length of 195mm. Thermocouple type K are installed on the heater jacket wall and fluid. Convective heat transfer is transiently calculated with constant heat flux. The research results show that in the first phase, there is a significant increase in heat flux of 512.82 W/m2, 769.23 W/m2, and 1025.4 W/m2, respectively, at rates of 0.34, 0.46, and 0.61 ℃/minute. In phase 4, the temperature increase is relatively small, with rates of 0.01, 0.02, and 0.03 ℃/minute, respectively. Heat transfer coefficients (h), Nusselt numbers (Nu), and Rayleigh numbers (Ra) increase with increasing heat flux.